Pengaruh motivasi belajar dan metode pembelajaran pada masa tatap muka terbatas terhadap kemandirian belajar matematika siswa SMK - Ila Hilyatul Aen; Syamsuri Syamsuri; Abdul Fatah (Universitas Sultan Ageng Tirtayasa, 2023)
Abstract: Motivation in learning is very important because it also affects the success of learning. Learning motivation is related to independent learning. If there is a strong learning motivation in students, it will create an attitude of independent learning from within students. Independent learning is also influenced by student learning methods carried out with the teacher. In the implementation of any learning method, it is always necessary for each student to learn independently. During the Covid-19 pandemic the learning method applied was limited face-to-face learning, namely learning that was carried out face-to-face and online. This study aims to determine whether there is a positive and significant influence between learning motivation on the independence of learning mathematics in SMK students and whether there is a positive and significant effect between learning methods during the limited face-to-face period on the mathematics learning independence of SMK students. To answer these problems, an ex post facto research with a quantitative approach was conducted at SMK Negeri 1 Serang City. Sampling was done by random sampling technique as many as 518 students and then analyzed by the application of SEM-PLS. The results showed that learning motivation had a positive and significant effect on students' mathematics learning independence, the structural model coefficient value of 0.469. The higher students' learning motivation will make students more independent in learning mathematics. The results also show that the learning method has a positive and significant influence on the independence of learning mathematics with a structural model coefficient value of 0.418. The better and the quality of the learning methods applied, the higher the students' independence in learning mathematics. This study also revealed that learning motivation and learning methods can explain students' mathematics learning independence by 0.615 or 61.5%. So it is possible that students' mathematics learning independence is explained by other factors of 0.385 or 38.5%. With the results of this study, it is strived to continue to grow students' learning motivation and direct the learning methods applied to be more varied to increase the independence of learning mathematics for SMK students.